Valuing wildfire smoke–related mortality benefits from climate mitigation - Minghao Qiu; Christopher W. Callahan; Iván Higuera-Mendieta; Lisa Rennels; Bryan Parthum; Noah S. Diffenbaugh; Marshall Burke (Proceedings of the National Academy of Sciences, 2026)
Human-induced climate change has increased wildfire risks, associated air pollution, and health damages in North America. Despite its large potential for damage, climate-induced wildfire smoke is rarely incorporated in estimates of the societal costs of climate change. We develop an integrated framework to estimate air pollution from climate-induced wildfire smoke (fine particulate matter, PM 2.5 ) and the associated mortality damage in the United States across different trajectories of greenhouse gas emissions and global mean surface temperature. Our framework accounts for fire–vegetation feedbacks by empirically estimating the effects of past fires on future burn probability. Under 3 °C of global warming (relative to 1850–1900), we estimate that smoke exposure will lead to 64,000 deaths annually in the United States (95% CI: 33,500 to 112,300; calculated using historical population), a 60% increase above estimated annual smoke deaths during 2011-2020. Limiting global warming to 2 °C reduces smoke-related mortality by 14% (8,900 deaths per year) relative to our estimate for 3 °C. For every additional tonne of CO 2 emissions in 2025, we calculate a net present value of monetized damage (i.e., a partial social cost of carbon) of $11.2 (95%CI: − $1.1 to $41.6; 2020USD) due to climate-induced wildfire smoke mortality in the United States. Incorporating wildfire smoke damages into existing nonwildfire damage estimates increases the US domestic social cost of carbon by 74%, substantially increasing the expected benefits of greenhouse gas mitigation within the United States.